Exploring the distances people walk to access public transport - van Soest, Dennis; Tight, Miles R.; Rogers, Christopher D. F. (Transport reviews, 2020)
A shift from private motorised transport to more active transportation can, among other things, deliver significant health benefits. The main disadvantage of active transport (in particular walking) for most people compared to private motorised transport is the limited range. Public transport (PT) can complement the use of active modes and extend their range. Therefore, there might be potential to increase physical activity through an increase in PT use. This article takes a closer look at how walking relates to the use of PT by examining existing literature on the topic. It aims to study how far people walk to and from PT and what key factors influence this. Scopus, Transport Research International Documentation and Web of Science have been searched systematically for relevant articles, conference papers and books. After screening of titles and abstracts, 41 relevant publications were identified. Studies were included if they quantified the amount of walking (measured as either distance or time) that is directly related to the use of PT. Studies that quantified walking using general measures of daily physical activity or daily walking or that used stated preference designs were excluded. The PT systems considered in this paper are mass transport systems in urban areas, either road- or rail-based, with fixed schedules and stops. Demand responsive transport services, which can offer door-to-door travel, are not considered, as these systems can to a large extent eliminate the need to walk. In the identified publications, a large variety of walking distances and times have been reported, and these seem to be highly context-specific. The paper establishes the evidence for the wide range of factors that influence walking related to PT, which have been categorised as personal, PT-related, environmental, and journey-related. The different methods that have been used are discussed by critically analysing their advantages and limitations. Only a limited number of these methods used allow for an accurate assessment of the walking distances to and from PT. The paper concludes with suggestions for future research, such as a need for more accurate measurement of walking and research in different geographical areas to shed light on underlying influences of culture and climate.